Analisis Kelembagaan Mal Pelayanan Publik Kabupaten Banjar - Syarani, Ridwan; Malawat, Sitna Hajar; Akhmad, Beni; Utomo, Haris (SENGKUNI Journal (Social Science and Humanities Studies), 2025)
Public Service Mall (MPP) is a public service management unit at the Regency/City level whose operations involve several stakeholders. This multi-stakeholder institution certainly requires a solid and agile institution so that the service process runs well according to what is planned and determined. The results of the institutional evaluation are one of the benchmarks for the success of the MPP. The MPP institution, which is coordinated by the Investment and One-Stop Integrated Services Office, has not been comprehensively evaluated. The results of the MPP institutional analysis are expected to provide input for improving the operations of public service institutions in the future. The design of data collection techniques was carried out through interviews and literature, the design of data analysis used analytical qualitative analysis techniques, especially through the perspective of the institutional development framework. The Public Service Mall institution as a whole is the embodiment of the relationships between institutional variables and forms the final part of the institutional process itself. In the institutional process, all elements of linkage or interrelationships between institutional variables are well depicted in the Banjar Regency MPP. Institutionalization as an evaluative variable is the objective of the standard for assessing the success of institutional development efforts at the MPP of Banjar Regency, as reflected in the operational running of services from the beginning of its formation until now.